Molecular Detection of Lysinibacillus Fusiformis Isolated from Milk Samples of Cow in Iraq - Aseel Mohammed Hamzah (Journal of Global Pharma Technology, 2016)
Raw milk  infected by bacteria can start from exceptional resources: air, milking devices, feed, soil, dangs and hays.The strategies of  nourishing and lodging cows may impact the germs pleasant of milk. Bacterial contaminants can cause infection, or deterioration of drain and its auxiliary items and the destructive impacts on the grade and security of dairy items as a result of oxygen consuming spore-forming bacteria got from crude drain were characterized by isolation of Lysinibacillus fusiformis from 90 milk samples of cow at 21.6l%, the bacteria were identified by routein bacteriological methods and Molecular distinguishing proof of the confines was carried out by 16S rRNA sequencing and the bacterial confines were taxonomically classified as Lysinibacillus fusiformis. The groupings were stored in NCBI GenBank with the accession number KY038703, KF916675. and KF916675.1 with identity of 100%, 96 and 99% respectively. Keywords: Raw milk, Lysinibacillus fusiformis, 16S rRNA PCR sequencing.